Simultaneous Determination Of Metamizole, Thiamin And Pyridoxin In Multicomponent Tablet by RP-HPLC - Chotimah, Chusnul (Fakultas Farmasi, Universitas Gadjah Mada, 2014)
The aim of the study was to develop and validate high performance liquid chromatography (HPLC) assay for the simultaneous determination of Metamizole, Thiamine and Pyridoxin in multicomponent tablet dosage form. The experimental procedure involved reversed-phase-HPLC with a Atlantis T3 C18 column (5 μm particle size, 4.6 ID x 150 mm), PIC solution-metanol-acetic acid volumetric solution (700: 300 : 4, v/v/v) mobile phase, UV detection at 275 nm. The flow rate of the mobile phase was 1.2 mL/min. The method was validated with respect to specificity, precision, accuracy and linearity. Due to its simplicity and accuracy, the assay method is suitable for routine analysis of multiomponen tablet formulation. Key words : metamizole, thiamine, pyridoxin, HPLC